Chromatographic Cake as a Strong Tool for Intact Protein Purification Dominated by “Steady Migration” of Two Variables in Preparative Scale by Liquid Chromatography - Mingtao Geng; Yunjun Lu; Gang Chen; Fei Wang; Xindu Geng (Current Overview on Science and Technology Research Vol. 8, 2022)
The purpose of the presented investigation is that how a short chromatographic column works and why there are more advantages from a chromatographic cake than that from a conventional long column in preparative scale. Based on the new principle of “steady-migration” of biopolymer separation in liquid chromatography (LC), A new approach termed “five-S” strategy is presented for fast, high-resolution separation of proteins on a preparative scale. The five-S strategy involves a Short column of very large diameter termed the chromatographic cake (or just cake). This is packed with very Small particles for protein separation under Small overloading per unit cross-Sectional area of the packed bed at a Suitably low linear velocity. The high density of the cake bed, which is packed in a direction perpendicular to that of the mobile phase flow, greatly reduces the protein band broadening. Using the chromatographic cake, the protein density per unit cross-sectional area of the cake bed decreases substantially, and protein separation that originally occurred under conventional nonlinear liquid chromatography conditions now proceeds under conditions similar to those of ideal linear liquid chromatography. The five-S strategy was tested by performing preparative-scale separation of standard proteins using a silica-based hydrophobic interaction chromatography (HIC) packing at different mobile phase flow rates. In comparison to conventional columns, better resolution with simultaneously faster separation was achieved on the cake even under higher overload conditions.